An integrated theoretical-experimental approach to understand facilitated proton transfer-electron transfer coupled reactions at thick-film modified electrodes - Zanotto, Franco Martín (2018)
The main purpose of the current work is to generalize the analytical model for the facilitated proton transfer-electron transfer coupled reactions at thick organic film-modified electrodes, including ion pairing in the organic phase and considering non-ideal electrolyte solutions in both phases. The main equations to calculate half-wave potentials developed in this model allow the simulation of different chemical systems, comprising hydrophilic and hydrophobic neutral weak bases, at different experimental conditions such as pH, organic phase to aqueous phase volume ratio, and concentration ratios between the redox probe and the transferring protonated species. The model was checked against experimental voltammetric responses measured with the transfer of Tylosin A at the water|1,2-dichloroethene interface. Consequently, we present here an integrated theoretical-experimental approach in order to compare the results of our previous model [Zanotto et al. Electrochim. Acta 258 (2017) 727?734] with experimental data from Tylosin A and predicted half-wave potentials.